Aprendizagem invertida na educação superior : o processo de mediação pedagógica nas humanidades - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The context of digital culture has had an influence on different fields of society, including education. This has resulted in new reflections on the process of pedagogical mediation, based on a scenario of ruptures in new perspectives regarding times and spaces for teaching and learning. In this reality, emergent pedagogies appear, such as the Flipped Learning (FL), which started to gain space within the pedagogical practice. This research aimed to analyze and discuss how the processes of pedagogical mediation have been explored in the scientific literature in the planning and implementation of Flipped Learning in the context of the Humanities in higher education. Given the low number of national publications on the subject, we opted for exploratory and bibliographical research, contemplating a traditional and systematic literature review. To this end, we discuss the pedagogical mediation process and its relationship with new possibilities based on digital information and communication technologies (DICT), blended learning principles. From that, FL is conceptualized and characterized based on Talbert (2017), Bergmann and Sams (2014; 2015), the Flipped Learning Network (FLN, 2014), and the Academy of Active Learning Arts and Sciences (AALAS, 2020a), also addressing FL's history and proposals that support it. Based on this understanding, a systematic literature review was carried out in order to analyze and reflect on the processes of pedagogical mediation in the implementation of FL in undergraduate and graduate courses in the context of the Humanities. It is noticed that the topic is still not very significant in the literature and, sometimes, without exploring the pedagogical processes in depth. From the analysis carried out, it is discussed how the teacher's work has been taking place in the mediation of the different moments of FL, addressing before, during, and after the class or meeting between students and teachers. It was observed that, despite the benefits and results presented, FL encompasses a process that demands a large amount of time and work, mainly concerning curation, selection, and/or creation of resources, materials, and content, in addition to the teacher's work in pedagogical mediation. On the other hand, reflections are presented about ways and possibilities for planning and implementing the proposal so that the teaching-learning process takes place. In this research, we also discuss the silences about pedagogical mediation in FL in the scientific literature.
Flipped learning in higher education: the pedagogical mediation process in humanities
Keywords: Educação superior - Sala de aula invertida; Mediação pedagógica; Ensino híbrido; Educação superior - Aprendizagem invertida; Higher education - Flipped classroom; Pedagogical mediation; Blended learning; Higher education - Flipped learning; CIENCIAS HUMANAS::EDUCACAO